Improving Secondary School Students’ Achievement in Circle Geometry using Blended Learning - Monique Abongkeyung Newen; Nfor Julius Cheny (Researchparks Publishing, 2023)
This study was designed to determine how students’ achievement in Circle geometry can be improved using blended learning. This study employed a quasi-experimental research design involving non-equivalent control group design. The area of the study was Bamenda III Council area of the North West region of Cameroon. The sample for this study consisted of ninety five (95) form four students from two private college composed using multi-stage sampling procedure. Through purposive sampling technique, Bamenda III Council Area was selected for this study because of the availability of private schools with computer laboratories and internet facilities in this area. Purposive sampling technique was used to select two private schools from Bamenda III Council area that shared common characteristics in terms of availability of internet facilities and computers in the schools and willingness of the school authorities to allow for the conduct of such an experiment. In each school, one class in a stream of classes at the same level was drawn through simple random sampling technique. Simple balloting was employed to draw the students in each school. The research instrument was Circle Geometry Achievement Test (CGAT) developed by the researchers. The internal consistency of CGAT was determined using Kuder Richardson, K.R. 20 and the calculated index was found to be 0.79. Students in both groups were pretested and post-tested. Scores from these instruments were analyzed using means and standard deviation to answer research questions and analysis of covariance (ANCOVA) to test the hypotheses. Some of the major findings from the analysis were: (i) Blended Learning improved students’ achievement in Circle geometry. (ii) Blended Learning favoured the female students in terms of achievement. Based on the findings, recommendations were made towards better achievement of students in Circle geometry particularly and Mathematics in general. It was recommended among others that secondary and primary school mathematics teachers should adopt Blended Learning as a teaching strategy. Another recommendation was that curriculum planners should incorporate Blended Learning into curriculum design during review of curricular contents.